Analysis of rabbit cell surface (CD) antigens by means of cross-reactive monoclonal antibodies with specificity for cattle CD antigens - Simon, M.; Antalíková, J.; Horovská, Ľ.; Jankovičová, J.; Fábryová, K.; Hluchý, S.; Chrenek, P.; Tančin, V. (Czech Journal of Animal Science, 2009)
Studies that involved testing monoclonal antibodies (mAbs) for cross-species reactivity proved to be efficient for the identification of previously unrecognized antigens in a number of different species. Twenty-six mAbs specific to different bovine CD (cluster defined) antigens (CD9, CD18, CD45R, CD41/61, CD62L, MHC class I and bovine IgG light chain molecule) were assayed for reactivity with rabbit peripheral blood leukocytes. Four of the mAbs recognizing CD9 and CD41/61 were reactive with rabbit platelets or granulocytes. These were investigated further by immunoblotting and immunohistochemical staining. The study identified CD9 and CD41/61 molecules on rabbit cells by mAbs IVA-50 and IVA-38. It showed that IVA-50 is a new valuable CD9 reagent for rabbit immunology which could be used for immunofluorescence staining or ELISA assay, immunohistological and molecular studies of rabbit CD9 antigen. IVA-38 recognizes the CD41/61 on rabbit platelets in indirect immunofluorescence and ELISA assay.
Keywords: blood cells; tissue; CD9; CD41/61